LEXICAL MEANS OF EXPRESSION OF TEMPORALITY IN THE VERSION OF THE MODERN UKRAINIAN LANGUAGE AT THE END OF THE XIX CENTURY (BASED ON LETTERS FROM VASYL STEFANYK) - Rusakova, Olha (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Aim. The article is devoted to the analysis of the means that represented lexical temporality in the modern Ukrainian language (in its western version) in the last decades of the XIX century. The purpose of the article is to determine the peculiarities of the functioning of the means of expression of lexical temporality, to classify words with temporal semantics on the material of the epistolary of Vasyl Stefanyk for 1888 – 1898. Methods. The paper uses a systematic approach using the lexical-semantic method of research of language units, the method of continuous sampling. Results. The article presents the lexical-semantic classification of words for the designation of time by two lexical-grammatical parts – nouns and adverbs, and features of functioning of temporal lexemes in the texts of Vasily Stefanyk’s letters are revealed. The analysis has shown that all lexical means of temporality expressing can be classified within three microclusters: lexical means with a clear indication on the time of year or day, a specific date, hour and religious holiday; lexical specifiers with chronological semantics without a clear indication of the exact time; a combination of the words of the language different independent parts employed by the author of the letters to point the approximate time or more detailed description of the event time. Scientific novelty. The article for the first time analyzes the specifics of Vasyl Stefanyk’s use of words with temporal semantics in letters, lexical-semantic classification of such words through the prism of the Western version of the modern Ukrainian language in the last decades of the XIX century. Practical meaning. The material of the article can be used in further study of the category of lexical temporality in the modern Ukrainian language, as well as in the study of the Galician language at the turn of the XIX - XX centuries.